Incidencia de los ratios financieros de la Ferretería Vélez Salazar Andrea del Carmen tras la época de pandemia en el período 2020 – 2021. - Castro Briones, Diego Armando (2022)
Disensa began commercial operations on February 27, 2012 under the RUC number 1103936710001, under the company name Vélez Salazar Andrea Del Carmen. It is located in the town of Loja, on Sucre SN and Carlos Román streets. Financial ratios help determine whether a company, whether small or large, is ready to pay its debts in a certain period of time, generally in the short or medium term, because solvency is of value to entities, capable of measuring the speed and efficiency of a company's payments. An analysis will be carried out with the financial statements of the Disensa hardware store, using the knowledge acquired in the course of the work, both the internet tools and the bibliographic content to achieve maximum optimal sustainability and thus help improve decision-making. hardware store with an in-depth review of bibliographic and reference content to support the scientific knowledge that makes financial analysis a reality, allowing the calculation of financial statements through billions of businesses that are on the right track financially. The economic variation of the Disensa hardware store depends mainly on the purchase and sale of goods, which for them are stocks, accounting speaking, that they keep to carry out their economic activities and to increase profits, they depend a lot on their circulation and control, if they are not sold, you don't win. With this pandemic, merchandise turnover has been affected, which has translated into lower sales during and after the pandemic.